GAMIFIKASI BAHASA: MEDIA LITERASI UNTUK SISWA TINGKAT MADRASAH IBTIDAIYAH DI MASA PANDEMI - Taufik Arochman; Muhammad Daniel Fahmi Rizal (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
One of the ways to achieve literacy skills at Madrasah Ibtidaiyah is with the help of the media. Media literacy in learning is applied to improve the quality of students' listening, reading, writing, and speaking as well as media capable of gaining knowledge. One of the media literacy that can be applied in learning is language gamification activities. The objective of this study was to determine the extent of the benefits of language gamification for students at Madrasah Ibtidaiyah. The method of the research is qualitative, with research data collection techniques using participatory observation, interviews, and documentation. This research was conducted at MI Al Islam Balesari Magelang, with the research subjects were students in grades 3A and 3B with a total of 38 students. The data collected were analyzed and presented descriptively. The activities were carried out online considering the pandemic is still ongoing. The results of this study were, first, the process of using language gamification as a media for student literacy varies with the aim of enriching student vocabulary and, second, language gamification has a positive impact as a media for literacy for students at MI Al Islam Balesari. The activities were carried out effectively and the intended results were very good